2014
DOI: 10.1080/03075079.2013.868878
|View full text |Cite
|
Sign up to set email alerts
|

Making judgements: investigating the process of composing and receiving peer feedback

Abstract: Recent studies have argued that tutor feedback is failing to support students' progression. The potential for peer feedback, i.e. feedback composed by peer assessors, to support learning has been under researched. The aim of this paper was to explore a case study of a peer assessor composing and receiving peer feedback. The paper reports a case study tracking a peer assessor through the process of grading and composing peer comments and her reactions to receiving peer feedback. The data consist of feedback com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 26 publications
3
60
0
2
Order By: Relevance
“…This may restrict the potential for development of skills that will impact on the 'other half' of the peer review process -changing content in response to feedback (McConlogue 2014). While the first three categories assessed here tend to relate to analytical skills, this research also sought to test communication skills associated with peer review, including whether feedback is constructive and balanced, justified with examples to enhance transparency and likely to result in improvement of the final product against assessment criteria -key peer review learning outcomes identified by Pearce, Mulder, and Baik (2009).…”
Section: Quality Of Peer Review Feedback Commentsmentioning
confidence: 97%
“…This may restrict the potential for development of skills that will impact on the 'other half' of the peer review process -changing content in response to feedback (McConlogue 2014). While the first three categories assessed here tend to relate to analytical skills, this research also sought to test communication skills associated with peer review, including whether feedback is constructive and balanced, justified with examples to enhance transparency and likely to result in improvement of the final product against assessment criteria -key peer review learning outcomes identified by Pearce, Mulder, and Baik (2009).…”
Section: Quality Of Peer Review Feedback Commentsmentioning
confidence: 97%
“…With respect to the learning mechanisms involved in the peer feedback process, some prior studies have differentiated between providing and receiving peer feedback on academic writing (e.g. Cho and MacArthur 2011;Greenberg 2015;McConlogue 2015;Nicol, Thomson, and Breslin 2014). To our knowledge, however, a direct (quasi-)experimental comparison of the impact that providing versus receiving peer feedback has on students' learning gains is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, reflection is reinforced because, when articulating an evaluation judgment, the feedback provider must offer a coherent explanation. Although peer feedback is also mediated by students' perceptions of the critique they have received [17,23], typically students perceive the benefits of providing feedback rather than receiving it [17,24,25]. Generally, in mediating peer feedback, students who provide and receive feedback are more motivated when seeing themselves totally involved in the activities undertaken in class [21].…”
Section: Introductionmentioning
confidence: 99%